Leaders of change: Children and the climate change movement - Karacaoglu, Beyza; Akbaba, Mehmet Fatih (YILDIZ TECHNICAL UNIV, 2024)
Climate change is a global crisis associated with the increase in greenhouse gas emissions and is associated with many environmental, psychological, and health problems today. One of the problems of the past, present, and future is children's limited knowledge about climate change and their inability to take an active role as participants in the struggle. Children are the greatest pioneers of change, and their ability to change the world is undeniable. Children need to know the facts about climate change, make their voices heard in climate crisis management, and be involved in the struggle. In this regard, it is crucial to conduct various sustainability trainings and activities, both in school and after school, using effective communication strategies. These strategies should include explaining and conveying climate change using positive language, utilizing methods such as localization, visualization, and storytelling with children. In the meantime, it is very important that educators, families, and society also gain awareness and become equipped about climate change, and that children take responsibility and become active participants, because the fight against climate change is intergenerational and climate change has mutual effects on attitude and behavior change. The scope of this review is to examine the role of children in combating climate change and to compile literature studies and real-life examples to understand the importance of the subject. This study will make an original contribution to different communication strategies and educational programs that present solutions to the climate crisis, as well as lead the way for families and communities to guide children.
Keywords: Awareness; Children; Climate Change; Communication; Education; MORAL JUDGMENTS; MENTAL-HEALTH; YOUNG-PEOPLE; CHILDHOOD; ACTIVISM; PARENTS; GAMES; Engineering